2020
DOI: 10.33155/j.ramd.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Wake Cycle of Elite Athletes Prior to the Rio 2016 Olympic Games

Abstract: Objective: To analyze chronotype, duration and quality of sleep among elite athletes, to compare differences in sleep variables between sex, and to compare differences between athletes of individual and team sports. Method: The sample included 70 Brazilian elite athletes of both sex (male=37; female=33) with a mean age 23.0 ± 4.0 years old. To measure sleep-wake cycle, athletes wore an actigraph on the wrist for 10 days. Moreover, athletes answered the chronotype questionnaire of Horne and Östberg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…From this perspective, Narciso et al [17] [16,17], which may be a concern for the health area and the technical committee of the teams, considering that the low quality of sleep or insufficient sleep can be related to injuries in soccer athletes, for example [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From this perspective, Narciso et al [17] [16,17], which may be a concern for the health area and the technical committee of the teams, considering that the low quality of sleep or insufficient sleep can be related to injuries in soccer athletes, for example [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding subjective parameters, two studies [17,25] demonstrated that the most predominant chronotype is the indifferent one (78% and 64%, respectively), while one study [18] presented a 22% prevalence of daytime sleepiness. Subjective poor sleep quality was 49% in one of the studies [18] and 53% in the other study [19], demonstrating that from a combined sample of 263…”
Section: Sleep Parametersmentioning
confidence: 99%
See 3 more Smart Citations